Nikos Kazantzakis and the Cretan Question during the Period of the Cretan State (1898-1913) - Χαλκιαδάκης Εμμανουήλ Γ. (Education Sciences, 2019)
This paper aims to present Nikos Kazantzakis’ thoughts and political ideas as far as the Cretan Question is concerned, with specific interest in the transition period of the Cretan State (1898-1913), a period of an ostensible Autonomy. For Kazantzakis and other Christian Cretans, the appointment of Prince George as High Commissioner of the Cretan State was the first step towards the Union of Crete with Greece. That’s why the welcoming of Prince George by the enthusiastic crowds in Crete was unrepeatable. Kazantzakis, during his studies in the University of Athens and after his graduation, was highly interested in the political future of Crete and believed that the Christian Cretans should continue their “ultimate effort» for Union. Public and private archival collections and especially the study of Pantelis Prevelakis about Kazantzakis’ biography and the study of Martha Aposkitou – Alexiou about the 34 unknown letters of Kazantzakis to his classmate Charilaos Stephanidis, when they both attended Heraklion High School, have proven very useful for this study.